Sistem Pakar Diagnosis Penyakit Gigi pada Anak Usia 5-12 Tahun Menggunakan Metode Forward Chaining - Florinza, Anastasia Revina; Setiawan, Lukas Anthony; Andriliana, Anniza Sukma; Oktavia, Nova; Miftachusurur, Miftachusurur; Yunita, Farida (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2024)
Children's dental health is a crucial aspect that must be carefully attended to, as despite being the hardest tissue in the human body, teeth are highly susceptible to bacterial attacks. Many parents neglect their children's dental health, mainly due to limited economic resources and insufficient knowledge about the importance of early dental care. Dental diseases in children can lead to more severe health problems if not properly treated. Therefore, a system is needed to help detect dental problems in children at an early stage. This expert system for diagnosing dental diseases in children is designed to replicate the thought process of a dentist in diagnosing dental issues based on symptoms inputted by the user. This study uses the forward chaining method, which is reliable in accurately identifying dental problems and providing early treatment recommendations, as well as oral health information. The system is expected to assist parents in detecting their children's dental issues and offering appropriate recommendations before consulting a dentist. Furthermore, this system has the potential to be used in clinics or health centers to support the dental diagnosis process more quickly and efficiently.